Apolipoprotein M (ApoM) involved in the Nile tilapia (Oreochromis niloticus) against Streptococcus agalactiae infection - Xuyan Tan; Yongxiong Huang; Zhiqiang Zhang; Yuhang Dong; Kwaku Amoah; Yu Huang; Jichang Jian (Aquaculture Reports)
Apolipoprotein M (ApoM) is a type of apolipoprotein in the bloodstream, with a primary affinity for high-density lipoprotein (HDL). It exhibits tissue-specific expression and performs a variety of biological functions, including lipid transport and metabolism, as well as antibacterial and anti-inflammatory effects. In order to elucidate the immune mechanism of ApoM in fish, we initiated the cloning of the ApoM gene in the widely studied Nile tilapia (Oreochromis niloticus) (On-ApoM) and examined its role during acute bacterial infection. The open reading frame (ORF) for On-ApoM encompasses 591 bp, encoding a protein of 196 amino acids. Notably, On-ApoM is mainly expressed in the liver of tilapia. After Streptococcus agalactiae stimulation, On-ApoM was activated to varying degrees in the liver, brain, spleen, head kidney, intestine, and other immune tissues of tilapia. While our study revealed that On-ApoM decreased bacterial load in the liver, On-ApoM again demonstrated the ability to inhibit inflammatory processes, consequently enhancing tilapia survival during acute bacterial infection. Alternatively, On-ApoM may play a role in modulating various immune pathways. These findings lay the groundwork for further exploration of the role of On-ApoM in fish immunity.